The thrifty guide to the American Revolution : a handbook for time travelers - Stokes, Jonathan W. (Stokes, Jonathan W. Thrifty time traveler's guide., 2018)
Provides useful information for the practical time traveler, including appropriate period dress, how to fire a musket, what to do if you are shot by one, and how to survive a stint in the Continental Army.